Optimization design method for mesh reflector antennas considering the truss deformation and thermal effects. (1st April 2020) - Nie, Rui; He, Baiyan; Yan, Shaoze; Ma, Xiaofei
Highlights: The performance optimization for antennas in the thermal environment is proposed. A thermal-structural model considering the truss deformation is established. The thermal effects on surface accuracy and tension distribution are discussed. Abstract: Mesh reflector antenna plays an important role in the future advanced satellite communication and broadcasting systems, earth observation, land sensing, deep space exploration, and space communication systems. The form of mesh surface is heavily dependent on cable tensions and vice versa. So, the form finding and optimization design of cable networks are extremely important. However, the current design methods conduct optimization under ambient temperature and ignore the shape errors caused by the thermal deformation in space thermal environment. The active on-orbit shape adjustment is limited by the on-orbit measurement and control techniques in the application. The present preliminary adjustment before launch only considered the cable network's thermal effects and ignored the influences of the truss elastic and thermal deformation on the surface accuracy. Here we proposed an optimization design method for mesh reflector antennas aiming at improving the surface accuracy and tension distribution in the space thermal environment. The truss model is established by adopting Euler-Bernoulli beams and the cable network is modeled based on Hooke's law. The deformation compatibility condition is applied to form the systematic model which is further applied in the optimization design. As the elastic and thermal deformation of the truss and the cable network, as well as their coupling effects, are fully considered in the design stage, the burden of shape adjustment for thermal errors can be relieved. Numerical examples show that the proposed method can effectively improve the surface accuracy in the temperature interval. The work provides the methodology for the reduction of on-orbit shape errors and the optimization design aiming at the performances in the space environment.